Analysis of energy and nutrient adequacy in two menu variants of the free nutritious meal (MBG) program for adolescents in Makassar City - Faramitha Faramitha; Hendrayati Hendrayati; Nadimin Nadimin (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
The Free Nutritious Meal (MBG) Program is a national initiative aimed at meeting students’ balanced nutritional needs. However, evidence on the adequacy of energy and nutrient intake from MBG menus for adolescents is limited. This study aimed to analyze the energy and nutrient adequacy of two MBG menu variants with and without milk based on the Recommended Dietary Allowances (RDA) for adolescents aged 16–18 years in Makassar. This cross-sectional study was conducted from August to September 2025 in four high schools that implemented the MBG program. Researchers conducted composite sampling of four daily menu items. Data were collected through menu observation and nutrient analysis using NutriSurvey. Univariate analyses were performed. The results indicated that the menu with milk provided 742 kcal (28% RDA) and 34.9 g of protein (46.5% RDA), whereas the menu without milk provided 610 kcal (23% RDA) and 28.4 g of protein (38% RDA). Both menus supplied more than 50% of the RDA for iron, but the carbohydrate contributions remained below 25% of the RDA. The low carbohydrate contribution suggests the need to adjust staple food portions in the MBG menu guidelines. In conclusion, the addition of milk improved the energy and protein adequacy of the MBG menus. The optimization of nutrient-dense local foods is recommended to support program sustainability and balanced nutrition in schools.